Assessing The Phylogeny Of Genus Dioscorea From Meghalaya (India) Based On Principal Component And Cluster Analysis (Applied Biological Research, 2019)
The present study examined the morphology, anatomy and palynological  characters of eight species of Dioscorea growing in Meghalaya (India). A  total of 128 characters of Dioscorea species were assessed using principal  component analysis (PCA) and cluster analysis methods. The first four principal components indicated 79.42% of the total observed variability.  Characters with discriminating values were stem twinning direction, position  of leaves, leaf apex shape, petiole colour, male flower colour, male floral  bracteoles shape, inner tepal shape of male flower, style shape, fruit shape,  seed shape, seed wing position, vascular bundle in outer ring, number of  paracytic stomata, breath of stomata, width of pollen aperture and orbicule  diameter. The cluster analysis clearly separated the species based on their  close association.
Keywords: Cluster analysis; Dioscorea; principal component analysis; traits